2015
DOI: 10.1111/ajad.12208
|View full text |Cite
|
Sign up to set email alerts
|

Prompted to treatment by the criminal justice system: Relationships with treatment retention and outcome among cocaine users

Abstract: Background and Objectives A substantial portion of individuals entering treatment for substance use have been referred by the criminal justice system, yet there are conflicting reports regarding treatment engagement and outcome differences compared to those not referred. This study examined baseline characteristic and treatment outcome differences among cocaine-dependent individuals participating in cocaine treatment randomized trials. Methods This secondary analysis pooled samples across five completed rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Probation plays a type of system navigator role through the referrals it provides, while also wielding the power to coerce clients to take-up necessary services. Most research evaluating the policy lever of coercion to induce treatment has ignored the role of probation departments, simply asking whether one was under probation supervision (J. F. Kelly et al, 2005; S. M. Kelly, O'Grady, Jaffe, Gandhi, & Schwartz, 2013; Kiluk et al, 2015;Marshall & Hser, 2002;Wild, Yuan, Rush, & Urbanoski). Other research has treated justice-related coercion as a unitary policy, ignoring the heterogeneity in how it is used (Farabee, Prendergast, & Anglin, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Probation plays a type of system navigator role through the referrals it provides, while also wielding the power to coerce clients to take-up necessary services. Most research evaluating the policy lever of coercion to induce treatment has ignored the role of probation departments, simply asking whether one was under probation supervision (J. F. Kelly et al, 2005; S. M. Kelly, O'Grady, Jaffe, Gandhi, & Schwartz, 2013; Kiluk et al, 2015;Marshall & Hser, 2002;Wild, Yuan, Rush, & Urbanoski). Other research has treated justice-related coercion as a unitary policy, ignoring the heterogeneity in how it is used (Farabee, Prendergast, & Anglin, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…M. Kelly et al, 2013;Kiluk et al, 2015;Perron & Bright, 2008). Some studies have been able to extend the time horizon beyond the index episode, typically measuring longer-term outcomes such as drug use or recidivism (J. F. Kelly et al, 2005;Kiluk et al, 2015). But because these studies start with a sample already in treatment and do not have information on the timing of the CS spell, they do not attempt to analyze the role of CS in inducing treatment.…”
Section: The Theory Of Coercionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Kiluk and colleagues (2015) found that adults referred to treatment by the criminal justice system (external motivation) had similar substance use treatment outcomes as those who were not. Our results suggest that the low problem recognition characterizing the Coerced Action group may be reflective of less drug involvement and their coerced action may be an appropriate response to substance use.…”
Section: Discussionmentioning
confidence: 99%